Skull Base Metastasis Revealed by Bone Scintigraphy in a Patient With Hypoglossal Nerve Palsy. (October 2018) - Katsanos, Aristeidis H.; Sioka, Chrissa; Chondrogiorgi, Maria; Papadopoulos, Athanasios; Fotopoulos, Andreas; Kyritsis, Athanassios P.; Ragos, Vasileios
Even though different imaging modalities are available in sole or in combination for the optimal detection of bone metastases, whole-body bone scintigraphy (BS) in a single session seems to be advantageous. We present an 80-year-old male with unilateral left hypoglossal nerve palsy (HNP) and no other focal deficits on neurological examination. Initial brain computed tomography (CT) scan revealed no pathological findings, while the subsequent cranial CT and magnetic resonance imaging (MRI) scans uncovered only mild nonspecific sclerotic lesions in left occipital condyle. All laboratory examinations were within normal limits, except for an elevated alkaline phosphatase (170 U/L) and a markedly increased prostate-specific antigen (609 ng/mL). The patient underwent whole-body BS with technetium-99m that revealed increased radiotracer deposition compatible with metastases in multiple foci, including the left occipital condyle. Prostate biopsy confirmed the diagnosis of prostate adenocarcinoma. Our case suggests that a complete and thorough workup for hidden malignancies should be performed in all patients with HNP, even in the absence of a finding in brain neuroimaging. Bone scintigraphy is an essential investigation that should be considered in uncertain cases of HNP, and especially in those with negative CT and MRI scans.